1970
DOI: 10.1530/jrf.0.0220461
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical Observations on the Mouse Uterus During the Oestrous Cycle

Abstract: Changes in the uterus of the mouse during the oestrous cycle have been examined histochemically to demonstrate any variation in the occurrence of acid phosphatase, lipids and polysaccharide com¬ plexes (PAS-positive material) mainly with reference to the epithelium. Acid phosphatase was shown to have a distinct pattern of activity at each stage of the oestrous cycle. There was no evidence for acid phos¬ phatase release, but a considerable build-up in large and small lysosomes was observed in the epithelium at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Earlier observations that the presence of lipids in the uterine epithelium of normal rats bears a direct relationship to the oestrous cycle, were based principally on the use of osmium (Alden, 1947 ;Fuxe & Nilsson, 1963) which stains lipids non-specifically (Drury & Wallington, 1967), Sudan black (Fuxe & Nilsson, 1963;Smith, 1970) which is non-specific for phospholipids (Pearse, 1968), and Scharlach R (Alden, 1947) which stains neutral lipids (Pearse, 1968). The techniques used in this study permit specific differentiation between intracellular lipids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier observations that the presence of lipids in the uterine epithelium of normal rats bears a direct relationship to the oestrous cycle, were based principally on the use of osmium (Alden, 1947 ;Fuxe & Nilsson, 1963) which stains lipids non-specifically (Drury & Wallington, 1967), Sudan black (Fuxe & Nilsson, 1963;Smith, 1970) which is non-specific for phospholipids (Pearse, 1968), and Scharlach R (Alden, 1947) which stains neutral lipids (Pearse, 1968). The techniques used in this study permit specific differentiation between intracellular lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of lipid metabolism in the uterine epithelium of the rat and the mouse during the oestrous cycle have shown that there is a cyclic production of lipids which is demonstrable histochemically (Alden, 1947;Elftman, 1958;Fuxe & Nilsson, 1963;Smith, 1970). Rat uterine lipid metabolism has also been investigated biochemically, using total uterine segments (Emmelot & Bosch, 1954;Davis & Alden, 1959;Aizawa & Mueller, 1961;Gorski & Nicolette, 1963;Nishigori & Aizawa, 1968).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation